Visiting professor program for environmental science: Does it contribute to student learning experience and problem-solving skills? - Anggi Tias Pratama; Rizqa Devi Anazifa; Nurul Bahiyah Abd Wahid (University of Muhammadiyah Malang, 2023)
This study reveals the contribution of student learning experiences and problem-solving skills in the Visiting Professor (VP) program. This research includes the type of ex post facto correlational research. The data collected in this study were learning experiences and problem-solving skills. Data collection techniques used a questionnaire to find out students' learning experiences on environmental change material, written essay tests to determine the ability to solve environmental pollution problems, and interviews with students on environmental change material. The results of this study found that the VP program had a relationship with and contributed to students' learning experiences and problem solving. The experience of the learning model in this VP gives the greatest contribution to problem-solving skills, followed by indicators of learning models based on student perceptions with percentages, indicators of learning resources with percentages, indicators of direct experience with percentages, indicators of substitute experience with percentages, and the last indicator that has a contribution the smallest is the indicator of student interaction with the percentage. The VP program should be carried out every semester in environmental science courses so that students get learning experience and problem solving. The next research that will be carried out is to look for other factors that influence and contribute to the VP program.